The Two-way Model of Creativity - Széll, Zsófia (Central European Journal of Educational Research, 2021)
Creativity is a term that has proven difficult to define. The field of English language teaching (ELT) especially struggles with this concept, often treating it as an axiom that eludes clear definition or a notion that everyone has an implicit understanding of. In other pieces of research, creativity is equated with divergent thinking as evidenced and measured by performance on different standardized creativity tests. In contrast to these views, this paper argues that sound research begins with a clear definition of key terms; as such, there is a need to establish a suitable model of creativity specifically for the field of ELT. After a review of notable existing views and definitions, a new model for creativity in ELT is outlined. The two-way model of creativity proposes that certain conditions enable creativity through specific tasks that allow for creativity to emerge. This will produce creative results that eventually have a reactive effect on the conditions.